Incidence of device-related infection in 97 750 patients: clinical data from the complete Danish device-cohort (1982–2018). (1st June 2019) - Olsen, Thomas; Jørgensen, Ole Dan; Nielsen, Jens Cosedis; Thøgersen, Anna Margrethe; Philbert, Berit Thornvig; Johansen, Jens Brock
Abstract: Aims: Device-related infection (DRI) is a severe complication to cardiac implantable electronic devices (CIED) therapy. Device-related infection incidence and its risk factors differ between previous studies. We aimed to define the long-term incidence and incidence rates of DRI for different types of CIEDs in the complete Danish device-cohort and identify patient-, operation- and device-related risk factors for DRI. Methods and results: From the Danish Pacemaker (PM) and implantable cardioverter-defibrillator (ICD) Register, we included consecutive Danish patients undergoing CIED implantation or reoperation from January 1982 to April 2018, resulting in 97 750 patients, 128 045 operations and follow-up of in total 566 275 device years (DY). We identified 1827 DRI causing device removals. Device-related infection incidence during device lifetime was 1.19% (1.12–1.26) for PM, 1.91% (1.71–2.13) for ICD, 2.18% (1.78–2.64) for cardiac resynchronization therapy (CRT)-pacemakers (CRT-P), and 3.35% (2.92–3.83) for CRT-defibrillators (CRT-D). Incidence rates in de novo implantations were 2.04/1000 DY for PM, 3.84 for ICD, 4.38 for CRT-P, and 6.76 for CRT-D. Using multiple-record and multiple-event per subject proportional hazard analysis, we identified implantation of complex devices (ICD and CRT), reoperations, prior DRI, male sex, and younger age as significantly associated with higher DRI risk. Conclusion: Overall risk of infection was low in PM implantations but considerably higher in CRT systems and after reinterventions. These data support the importance of evaluating all patients considered for CIED therapy thoroughly, in order to identify potential modifiable risk factors and reduce the risk of early reoperations.